2022
DOI: 10.1039/d2ta04433a
|View full text |Cite
|
Sign up to set email alerts
|

Surface engineering of a triboelectric nanogenerator for room temperature high-performance self-powered formaldehyde sensors

Abstract: The development of miniaturized self-powered gas sensors to achieve the real-time respiratory monitoring and analyses has tremendous clinical significance for early diagnosis. In this work, room temperature high-performance self-powered formaldehyde...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 87 publications
(143 reference statements)
0
16
0
Order By: Relevance
“…When exposed to the target chemicals, they should be able to interact with them in a certain way and show clear changes in their triboelectric characteristics. 44 A variety of materials, including conductive polymers, functionalized nanoparticles, and specially created composite materials, can be used. The operating mechanism of a TENG-powered Ti 3 C 2 T x /CuO-based gas sensor developed by D. Wang et al for the monitoring of NH 3 and TNEG has an I sc of 34 μA and a V oc of 810 V, shown in Fig.…”
Section: Applications Of Teng Devicesmentioning
confidence: 99%
“…When exposed to the target chemicals, they should be able to interact with them in a certain way and show clear changes in their triboelectric characteristics. 44 A variety of materials, including conductive polymers, functionalized nanoparticles, and specially created composite materials, can be used. The operating mechanism of a TENG-powered Ti 3 C 2 T x /CuO-based gas sensor developed by D. Wang et al for the monitoring of NH 3 and TNEG has an I sc of 34 μA and a V oc of 810 V, shown in Fig.…”
Section: Applications Of Teng Devicesmentioning
confidence: 99%
“…Currently, many life-relevant gas molecules have been detected by scientists trying to set up self-powered sensors, like ethanol, 145–147 NH 3 , 45,148,149 CO 2 , 150,215 NO 2 , 151 acetone, 152 formaldehyde, 154 etc. For instance, Fu et al 146 reported a 5 cm × 5 cm × 10 μm PENG-driven sensor array which is based on polyaniline/polyvinylidene fluoride (PANI/PVDF); it illustrated responses to acetone, ethanol, CO, NO x , and CH 4 with a concentration from 0 to 600 ppm and the maximum response of each sensing unit to 600 ppm of gas markers is 68.2%, 56.9%, 47.1%, 105.1%, and 53.5%, respectively.…”
Section: Applications Of Self-powered Biosensorsmentioning
confidence: 99%
“…To address the aforementioned issues, a straightforward strategy is to engineer the surface properties of triboelectric layers via chemical functionalization. 6,11,17–22 Through the incorporation of different functional groups on the surface of triboelectric layers, triboelectric properties can be finely tunable without affecting the bulk properties of the triboelectric layers. 11,17–21 For instance, we have demonstrated the feasibility of using self-assembled fluorinated molecules as the surface modification layer for PDMS, thereby significantly improving the TENG performance while maintaining excellent durability.…”
Section: Introductionmentioning
confidence: 99%